Silicon-carbon composite negative electrode material and preparation method thereof
By adopting a three-layer structure of modified graphite, silicon-carbon composite layer and carbon clad layer, a silicon-carbon composite negative electrode material was prepared, which solved the problem of large volume expansion effect of silicon-carbon negative electrode material in lithium-ion batteries, and achieved the effect of high energy density and long cycle life.
Patent Information
- Application Number
- CN202510081945.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-02-25
AI Technical Summary
In existing lithium-ion batteries, the volume expansion effect of silicon carbon anode material during the deliquification process is large, resulting in unstable battery structure and insufficient process adaptability, which limits its wide application.
A three-layer structure of the core layer, the intermediate layer and the shell layer is adopted. The core layer is modified graphite, the intermediate layer is a silicon-carbon composite layer, and the shell layer is a carbon clad layer. The silicon-carbon composite negative electrode material is constructed by the preparation method of modified graphite and nanoporous carbon composite material.
This material effectively buffers volume expansion during charging and discharging, improving structural stability and cycle life, and significantly improving the energy density and cycle performance of the battery.
Smart Images

Figure CN119517973A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery negative electrode materials, and in particular to a silicon-carbon composite negative electrode material and a preparation method thereof. Background Art
[0002] As an important part of modern energy storage technology, the selection of negative electrode materials for lithium-ion batteries has a decisive influence on battery performance. At present, graphite is the mainstream negative electrode material with a theoretical capacity of 372 mAh / g. However, with the development of technology, silicon-carbon negative electrode materials have attracted much attention due to their high lithium storage capacity (theoretical capacity is as high as 3580 mAh / g), and are expected to become the negative electrode material for the next generation of high energy density lithium-ion batteries.
[0003] However, silicon anodes face some challenges in practical applications. First, the volume expansion effect of silicon anodes during lithium insertion and extraction is much greater than that of graphite, which may lead to instability in the battery structure. Secondly, the slow development progress of lithium-ion battery systems and the lack of adaptability of battery cell preparation processes have limited the widespread application of silicon-carbon anode materials. Therefore, the current market is still dominated by graphite anode systems.
[0004] To overcome these challenges, the industry has adopted a physical mixing method, mixing silicon-carbon anodes into graphite in different proportions and preparing battery cells through conventional homogenization strategies. However, due to the differences in the surface interface between graphite and silicon-carbon anode materials, as well as the stability of the anode homogenization process, this composite method is prone to uneven dispersion of graphite and silicon-carbon in large-scale production, affecting the consistency of the battery cells and the efficiency of the battery cell process.
[0005] In addition, due to the uneven distribution of pole piece expansion stress, the battery may deform irregularly, and the local consumption of electrolyte may lead to accelerated battery cycle decay. These abnormal adverse phenomena not only affect the performance and life of the battery, but also greatly limit the application of silicon-carbon negative electrodes and the development and iteration of high-energy-density lithium-ion batteries.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] One of the purposes of the present invention is to provide a silicon-carbon composite negative electrode material, aiming to solve at least one of the above-mentioned technical problems in the prior art.
[0008] A second object of the present invention is to provide a method for preparing a silicon-carbon composite negative electrode material.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: A first aspect of the present invention provides a silicon-carbon composite negative electrode material including a core layer, an intermediate layer and a shell layer.
[0010] The material of the core layer is modified graphite, the middle layer is a silicon-carbon composite layer, and the shell layer is a carbon coating layer.
[0011] In the silicon-carbon composite negative electrode material, silicon accounts for 5-30wt%.
[0012] In the X-ray diffraction spectrum (Cu-Kα), the silicon-carbon composite negative electrode material forms diffraction peaks when 2θ is 26.5°, 28.4°, 45.0°, 47.5°, and 55.0°, wherein the ratio of the peak intensity at 2θ=26.5° to the peak intensity at 2θ=28.4° is ≤10, the half-peak width of the peak at 2θ=26.5° is 0.3°~0.8°, and the half-peak width of the peak at 2θ=28.4° is 0.3°~1.5°.
[0013] Furthermore, the particle size of the silicon-carbon composite negative electrode material is 2-50 μm.
[0014] Preferably, the silicon-carbon composite layer comprises porous carbon and silicon deposited in the pores of the porous carbon.
[0015] Preferably, the thickness of the porous carbon is in the range of 1-10 um.
[0016] Preferably, in the silicon-carbon composite negative electrode material, the proportion of porous carbon is 15-30wt%.
[0017] Preferably, in the porous carbon, the pore size is between 0.5 and 50 nm.
[0018] Preferably, the total pore volume in the porous carbon is 0.2-0.8 cm 3 / g.
[0019] Furthermore, the modified graphite includes at least one of carboxylated graphite, hydroxylated graphite, oxidized graphite and ammoniated graphite.
[0020] The second aspect of the present invention provides a method for preparing the silicon-carbon composite negative electrode material, comprising the following steps: A. Putting modified graphite particles and porous carbon precursor into a liquid phase reactor and mixing them evenly, and then spray drying to obtain a composite material of modified graphite and carbon precursor; B. transferring the modified graphite and carbon precursor composite material into a high temperature reactor to carbonize and activate the carbon precursor to obtain a micron-sized modified graphite and nanoporous carbon composite material; C. Passing silane gas into a high-temperature reactor containing the micron-sized modified graphite and nanoporous carbon composite material to form a silicon-carbon composite layer on the surface of the modified graphite; continuing to pass hydrocarbon gas into the reactor for carbon deposition and coating to obtain a silicon-carbon composite negative electrode material.
[0021] Furthermore, the preparation method of the modified graphite particles is: The graphite and the surface modifier are placed in a solid-liquid reactor, the graphite is subjected to surface modification treatment, and then dried to obtain modified graphite particles.
[0022] Preferably, the particle size of the graphite is 2-40 μm.
[0023] Preferably, the solid-liquid reactor comprises a tank reactor, a tubular reactor or a fluidized bed reactor.
[0024] Preferably, the surface modification temperature is 20-150°C.
[0025] Preferably, the drying method includes spray drying, flash drying, rotary drying, fluidized bed drying or vacuum drying.
[0026] Furthermore, the graphite includes artificial graphite and / or natural graphite.
[0027] Preferably, the natural graphite includes at least one of dense crystalline graphite, flake graphite and cryptocrystalline graphite.
[0028] Preferably, the surface modifier comprises an inorganic solution and / or an organic solution.
[0029] Preferably, the inorganic solution comprises hydrogen peroxide and / or nitric acid.
[0030] Preferably, the organic solution comprises a silane coupling agent.
[0031] Preferably, the functional group in the silane coupling agent includes at least one of ethoxy, amino, methacrylate, epoxy, mercapto, silicate, silicon oxide, fluorocarbon and alcohol.
[0032] Furthermore, the porous carbon precursor includes at least one of polyacrylonitrile, phenolic resin, melamine resin, epoxy resin, urea-formaldehyde resin, polyester resin, polyamide resin, polyimide resin, polycarbonate, and acrylonitrile copolymer.
[0033] Preferably, the specific surface area of the micron-sized modified graphite and nanoporous carbon composite material is 0.5-10 m 2 / g.
[0034] Preferably, the pores in the porous carbon include micropores and mesopores.
[0035] Preferably, the size of the pores in the porous carbon is 0.5-50 nm.
[0036] Preferably, the pore volume of the porous carbon is 0.2-0.8 cm 3 / g.
[0037] Furthermore, the silane-based gas includes at least one of monosilane, disilane, trichlorosilane and dichlorosilane.
[0038] Preferably, the hydrocarbon gas includes at least one of methane, ethane, propane, butane, ethylene, propylene and acetylene.
[0039] Furthermore, the liquid phase reactor comprises a pipeline reactor or a stirred tank.
[0040] Preferably, the temperature of the liquid phase reactor is 20-400°C.
[0041] Preferably, the high temperature reactor comprises a rotary kiln, a pusher kiln, a roller kiln, a box furnace or a tube furnace.
[0042] Preferably, the carbonization temperature is 400-1500°C.
[0043] Preferably, the activation is carried out by introducing an activation gas.
[0044] Preferably, the activation gas comprises at least one of carbon dioxide, flue gas, water vapor, air and oxygen.
[0045] Preferably, the activation temperature is 600-1200°C.
[0046] Furthermore, the temperature of the carbon deposition coating is 400-1000°C.
[0047] Preferably, the thickness of the carbon coating layer formed by carbon deposition coating is 0.5-50 nm.
[0048] Preferably, the carbon increment after carbon deposition coating is 0.1-5%.
[0049] Compared with the prior art, the present invention has at least the following beneficial effects: The silicon-carbon composite negative electrode material provided by the present invention adopts a three-layer structure of a core layer, an intermediate layer and a shell layer, wherein the core layer is modified graphite, the intermediate layer is a silicon-carbon composite layer, and the shell layer is a carbon coating layer. This structural optimization not only enhances the electrochemical performance and electrical conductivity of the material, but also effectively buffers the volume expansion of silicon during the charging and discharging process, thereby improving the structural stability and cycle life of the material. Secondly, the proportion of silicon is controlled at 5-30wt%, and the high theoretical capacity of silicon is utilized, which significantly improves the energy density of the battery while maintaining the stability of the material. In addition, X-ray diffraction analysis shows that the material successfully combines the advantages of silicon-carbon composite materials and graphite, and improves the electrical conductivity and structural stability of the material. The silicon-carbon composite negative electrode material not only improves the energy density of the battery, but also improves the cycle performance, providing strong technical support for the development of the next generation of high-performance lithium-ion batteries, and its design is compatible with the existing lithium-ion battery manufacturing process, which is conducive to promoting the commercialization process of new negative electrode materials.
[0050] The preparation method of the modified silicon-based negative electrode material provided by the present invention effectively modifies the graphite surface, introduces different surface active groups to enhance its surface activity, and lays the foundation for subsequent steps. Then, the nanoporous carbon is uniformly coated on the modified graphite surface through a bonding reaction to form a carbon layer that enhances the electrical conductivity and provides a carrier for the deposition of silicon. Subsequently, the modified graphite coated with nanoporous carbon is mixed with a silane gas under high temperature conditions, so that the silane gas is pyrolyzed and elemental silicon is deposited inside the pores of the porous carbon to achieve an integrated composite of silicon-carbon graphite. Finally, the surface of the composite material is subjected to a carbon coating treatment to reduce the surface activity of silicon and reduce side reactions, thereby obtaining a structurally stable and homogenized silicon-carbon-graphite integrated composite material, which provides new possibilities for the development of high energy density lithium-ion battery negative electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0052] Figure 1 SEM photos obtained for characterization example 1; Figure 2 To characterize the BSD photographs obtained in Example 1; Figure 3 To characterize the XRD pattern obtained in Example 3; Figure 4 The first cycle electrical performance curve obtained from the result example. DETAILED DESCRIPTION
[0053] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0054] A first aspect of the present invention provides a silicon-carbon composite negative electrode material including a core layer, an intermediate layer and a shell layer.
[0055] The material of the core layer is modified graphite, the middle layer is a silicon-carbon composite layer, and the shell layer is a carbon coating layer.
[0056] In the silicon-carbon composite negative electrode material, silicon accounts for 5-30wt%.
[0057] In the silicon-carbon composite negative electrode material, the proportion of silicon is 5~30 wt%; in the X-ray diffraction spectrum (Cu-Kα) of the silicon-carbon composite negative electrode material, diffraction peaks are formed when 2θ is 26.5°, 28.4°, 45.0°, 47.5°, and 55.0°, wherein the ratio of the peak intensity at 2θ=26.5° to the peak intensity at 2θ=28.4° is ≤10, the half-peak width of the peak at 2θ=26.5° is 0.3°~0.8°, and the half-peak width of the peak at 2θ=28.4° is 0.3°~1.5°.
[0058] The silicon-carbon composite negative electrode material provided by the present invention adopts a three-layer structure of a core layer, an intermediate layer and a shell layer, wherein the core layer is modified graphite, the intermediate layer is a silicon-carbon composite layer, and the shell layer is a carbon coating layer. This structural optimization not only enhances the electrochemical performance and electrical conductivity of the material, but also effectively buffers the volume expansion of silicon during the charging and discharging process, thereby improving the structural stability and cycle life of the material. Secondly, the proportion of silicon is controlled at 5-30wt%, and the high theoretical capacity of silicon is utilized, which significantly improves the energy density of the battery while maintaining the stability of the material. In addition, X-ray diffraction analysis shows that the material successfully combines the advantages of silicon-carbon composite materials and graphite, and improves the electrical conductivity and structural stability of the material. The silicon-carbon composite negative electrode material not only improves the energy density of the battery, but also improves the cycle performance, providing strong technical support for the development of the next generation of high-performance lithium-ion batteries, and its design is compatible with the existing lithium-ion battery manufacturing process, which is conducive to promoting the commercialization process of new negative electrode materials.
[0059] Typically but not limitatively, the proportion of silicon in the silicon-carbon composite negative electrode material can be 5wt%, 10wt%, 15wt%, 20wt%, 25wt% or 30wt%, or any value within the range of 5wt% to 30wt%.
[0060] Furthermore, the particle size of the silicon-carbon composite negative electrode material is 2-50 μm.
[0061] Typically but not limitatively, the particle size of the silicon-carbon composite negative electrode material can be 2 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, or any value within the range of 2 μm to 50 μm.
[0062] Preferably, the silicon-carbon composite layer comprises porous carbon and silicon deposited in the pores of the porous carbon.
[0063] Preferably, the thickness of the porous carbon is in the range of 1-10 um.
[0064] Preferably, in the silicon-carbon composite negative electrode material, the proportion of porous carbon is 15-30wt%.
[0065] Typically but not restrictively, in the silicon-carbon composite negative electrode material, the proportion of porous carbon can be 15wt%, 20wt%, 25wt% or 30wt%, or any value within the range of 15wt% to 30wt%.
[0066] Preferably, in the porous carbon, the pore size is between 0.5 and 50 nm.
[0067] Typically but not limitatively, the pore size in the porous carbon can be 0.5nm, 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, or any value within the range of 0.5nm to 50nm.
[0068] Preferably, the total pore volume in the porous carbon is 0.2-0.8 cm 3 / g.
[0069] Typically but not limiting, the total pore volume in the porous carbon can be 0.2 cm³ / g, 0.3 cm³ / g, 0.4 cm³ / g, 0.5 cm³ / g, 0.6 cm³ / g, 0.7 cm³ / g or 0.8 cm³ / g, or any value within the range of 0.2 cm³ / g to 0.8 cm³ / g.
[0070] Furthermore, the modified graphite includes at least one of carboxylated graphite, hydroxylated graphite, oxidized graphite and ammoniated graphite.
[0071] The second aspect of the present invention provides a method for preparing the silicon-carbon composite negative electrode material, comprising the following steps: A. Putting modified graphite particles and porous carbon precursor into a liquid phase reactor and mixing them evenly, and then spray drying to obtain a composite material of modified graphite and carbon precursor; B. transferring the modified graphite and carbon precursor composite material into a high temperature reactor to carbonize and activate the carbon precursor to obtain a micron-sized modified graphite and nanoporous carbon composite material; C. Passing silane gas into a high-temperature reactor containing the micron-sized modified graphite and nanoporous carbon composite material to form a silicon-carbon composite layer on the surface of the modified graphite; continuing to pass hydrocarbon gas into the reactor for carbon deposition and coating to obtain a silicon-carbon composite negative electrode material.
[0072] The preparation method of the modified silicon-based negative electrode material provided by the present invention effectively modifies the graphite surface, introduces different surface active groups to enhance its surface activity, and lays the foundation for subsequent steps. Then, the nanoporous carbon is uniformly coated on the modified graphite surface through a bonding reaction to form a carbon layer that enhances the electrical conductivity and provides a carrier for the deposition of silicon. Subsequently, the modified graphite coated with nanoporous carbon is mixed with a silane gas under high temperature conditions, so that the silane gas is pyrolyzed and elemental silicon is deposited inside the pores of the porous carbon to achieve an integrated composite of silicon-carbon graphite. Finally, the surface of the composite material is subjected to a carbon coating treatment to reduce the surface activity of silicon and reduce side reactions, thereby obtaining a structurally stable and homogenized silicon-carbon-graphite integrated composite material, which provides new possibilities for the development of high energy density lithium-ion battery negative electrode materials.
[0073] Furthermore, the preparation method of the modified graphite particles is: The graphite and the surface modifier are placed in a solid-liquid reactor, the graphite is subjected to surface modification treatment, and then dried to obtain modified graphite particles.
[0074] Preferably, the particle size of the graphite is 2-40 μm.
[0075] Typically but not limiting, the particle size of the graphite may be 2 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm, or any value within the range of 2 μm to 40 μm.
[0076] Preferably, the solid-liquid reactor comprises a tank reactor, a tubular reactor or a fluidized bed reactor.
[0077] Preferably, the surface modification temperature is 20-150°C.
[0078] Typically but not limiting, the surface modification temperature may be 20°C, 50°C, 80°C, 100°C, 120°C or 150°C, or any value within the range of 20°C to 150°C.
[0079] Preferably, the drying method includes spray drying, flash drying, rotary drying, fluidized bed drying or vacuum drying.
[0080] Furthermore, the graphite includes artificial graphite and / or natural graphite.
[0081] Preferably, the natural graphite includes at least one of dense crystalline graphite, flake graphite and cryptocrystalline graphite.
[0082] Preferably, the surface modifier comprises an inorganic solution and / or an organic solution.
[0083] Preferably, the inorganic solution comprises hydrogen peroxide and / or nitric acid.
[0084] Preferably, the organic solution comprises a silane coupling agent.
[0085] Preferably, the functional group in the silane coupling agent includes at least one of ethoxy, amino, methacrylate, epoxy, mercapto, silicate, silicon oxide, fluorocarbon and alcohol.
[0086] Furthermore, the porous carbon precursor includes at least one of polyacrylonitrile, phenolic resin, melamine resin, epoxy resin, urea-formaldehyde resin, polyester resin, polyamide resin, polyimide resin, polycarbonate, and acrylonitrile copolymer.
[0087] Preferably, the specific surface area of the micron-sized modified graphite and nanoporous carbon composite material is 0.5 to 10 m 2 / g.
[0088] Typically but not limitatively, the specific surface area of the micron-sized modified graphite and nanoporous carbon composite material can be 0.5m² / g, 1m² / g, 2m² / g, 3m² / g, 4m² / g, 5m² / g, 6m² / g, 7m² / g, 8m² / g, 9m² / g or 10m² / g, or it can be any value within the range of 0.5m² / g to 10m² / g.
[0089] Preferably, the pores in the porous carbon include micropores and mesopores.
[0090] Preferably, the size of the pores in the porous carbon is 0.5-50 nm.
[0091] Typically but not limitatively, the size of the pores in the porous carbon can be 0.5nm, 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, or any value in the range of 0.5nm to 50nm.
[0092] Preferably, the pore volume of the porous carbon is 0.2-0.8 cm 3 / g.
[0093] Typically but not limiting, the pore volume of the porous carbon can be 0.2 cm³ / g, 0.3 cm³ / g, 0.4 cm³ / g, 0.5 cm³ / g, 0.6 cm³ / g, 0.7 cm³ / g or 0.8 cm³ / g, or any value within the range of 0.2 cm³ / g to 0.8 cm³ / g.
[0094] Furthermore, the silane-based gas includes at least one of monosilane, disilane, trichlorosilane and dichlorosilane.
[0095] Preferably, the hydrocarbon gas includes at least one of methane, ethane, propane, butane, ethylene, propylene and acetylene.
[0096] Furthermore, the liquid phase reactor comprises a pipeline reactor or a stirred tank.
[0097] Preferably, the temperature of the liquid phase reactor is 20-400°C.
[0098] Typically but not limiting, the temperature of the liquid phase reactor may be 20°C, 50°C, 100°C, 150°C, 200°C, 250°C, 300°C, 350°C or 400°C, or any value within the range of 20°C to 400°C.
[0099] Preferably, the high temperature reactor comprises a rotary kiln, a pusher kiln, a roller kiln, a box furnace or a tube furnace.
[0100] Preferably, the carbonization temperature is 400-1500°C.
[0101] Typically but not limiting, the carbonization temperature may be 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C or 1500°C, or any value within the range of 400°C to 1500°C.
[0102] Preferably, the activation is carried out by introducing an activation gas.
[0103] Preferably, the activation gas comprises at least one of carbon dioxide, flue gas, water vapor, air and oxygen.
[0104] Preferably, the activation temperature is 600-1200°C.
[0105] Typically but not limiting, the activation temperature may be 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C or 1200°C, or any value within the range of 600°C to 1200°C.
[0106] Furthermore, the temperature of the carbon deposition coating is 400-1000°C.
[0107] Typically but not limiting, the temperature of the carbon deposition coating may be 400°C, 500°C, 600°C, 700°C, 800°C, 900°C or 1000°C, or any value within the range of 400°C to 1000°C.
[0108] Preferably, the thickness of the carbon coating layer formed by carbon deposition coating is 0.5-50 nm.
[0109] Typically but not limiting, the thickness of the carbon coating layer formed by carbon deposition coating can be 0.5nm, 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm or 50nm, or it can be any value in the range of 0.5nm to 50nm.
[0110] Preferably, the carbon increment after carbon deposition coating is 0.1-5%.
[0111] Typically but not limiting, the carbon increment after carbon deposition coating may be 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5%, or any value within the range of 0.1% to 5%.
[0112] The present invention is further described below by specific examples and comparative examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form. The raw materials used in the examples and comparative examples of the present invention, if no specific conditions are specified, are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0113] Example 1 This embodiment provides a silicon-carbon composite negative electrode material, comprising the following steps: 1. Put artificial graphite powder and concentrated nitric acid into a kettle reactor at a mass ratio of 1:3, heat to 300°C, keep warm for 12 hours, wash with deionized water to neutrality, and then dry in a vacuum dryer to obtain surface carboxylated graphite COOH-Gr; then put the carboxylated COOH-Gr into a stirring kettle filled with a phenolic resin aqueous solution with a solid content of 60% at a mass fraction of 15%, stir at a speed of 350r / min for 30 minutes and use 100kHz ultrasound for 4 hours to evenly disperse, then transfer to a water heating box at 90°C for constant temperature curing for 40 hours, and grind to a Dv50 of about 10μm by a pulverizer to obtain a graphite curing material coated with resin carbon.
[0114] 2. The solidified material was transferred to a pyrolysis rotary furnace, heated to 800°C at a heating rate of 10°C / min under a N2 atmosphere and kept warm for 6 hours, then transferred to an activation tube furnace, heated to 1200°C at a heating rate of 5°C / min under a H2O environment, and kept warm for 12 hours to obtain a porous carbon-coated graphite composite material.
[0115] 3. The porous carbon-coated graphite composite material is placed in a vertical fluidized bed. While continuously passing a N2 atmosphere for protection, monosilane gas is continuously introduced. The temperature is raised to 300°C at a heating rate of 5°C / min and kept warm for 9 hours to allow the mixed gas to evenly diffuse into the pores of the porous carbon on the graphite surface. The temperature is then raised to 500°C and chemical vapor deposition is performed for 12 hours to obtain modified graphite-doped porous carbon with deposited silicon nanoparticles, in which the silicon content is 25%.
[0116] 4. After the deposition is completed and the temperature is lowered, the modified graphite-doped porous carbon with deposited silicon nanoparticles is transferred to a carbon-coated rotary furnace. In an atmosphere of ethane and N2 mixed gas, the temperature in the furnace is raised to 700°C, and the graphite porous carbon composite material with deposited silicon nanoparticles is carbon-coated for 4 hours to obtain the graphite silicon-carbon integrated composite material, and the thickness of the carbon coating layer is 20 nm.
[0117] Example 2 This embodiment provides a silicon-carbon composite negative electrode material, comprising the following steps: 1. Put artificial graphite powder and hydrogen peroxide (H2O2) into a kettle reactor at a mass ratio of 1:3, heat to 60°C, keep warm for 12 hours, wash with deionized water to neutrality, and then dry with a vacuum dryer to obtain modified graphite O-Gr with rich oxygen-containing functional groups on the surface; then put the oxidized O-Gr into a stirring kettle filled with a phenolic resin aqueous solution with a solid content of 60% at a mass fraction of 15%, and evenly disperse it by stirring at 350r / min for 30 minutes and 100kHz ultrasound for 4 hours, then transfer it to a water heating box at 90°C for constant temperature curing for 40 hours, and grind it to a Dv50 of about 10μm by a pulverizer to obtain a graphite cured material coated with resin carbon.
[0118] 2. Same as the step in Example 1.
[0119] 3. Same as the step in Example 1.
[0120] 4. Same as the step in Example 1.
[0121] Example 3 This embodiment provides a silicon-carbon composite negative electrode material, comprising the following steps: 1. Put artificial graphite powder and amino-containing silane coupling agent (γ-aminopropyltriethoxysilane) into a kettle reactor at a mass ratio of 1:3, heat to 150°C, keep warm for 12 hours, wash with deionized water to neutrality, and then dry in a vacuum dryer to obtain surface amino graphite NH2-COOH; then put the surface amino graphite into a stirring kettle filled with a phenolic resin aqueous solution with a solid content of 60% at a mass fraction of 15%, stir at a speed of 350r / min for 30 minutes and use 100kHz ultrasound for 4 hours to evenly disperse, then transfer to a water heating box at 90°C for constant temperature curing for 40 hours, and grind to a Dv50 of about 10μm by a pulverizer to obtain a graphite curing material coated with resin carbon.
[0122] 2. Same as the step in Example 1.
[0123] 3. Same as the step in Example 1.
[0124] 4. Same as the step in Example 1.
[0125] Example 4 This embodiment provides a silicon-carbon composite negative electrode material, comprising the following steps: 1. Put artificial graphite powder and amino-containing silane coupling agent (N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane) into a kettle reactor at a mass ratio of 1:3, heat to 200°C, keep warm for 12 hours, wash with deionized water to neutrality, and then dry in a vacuum dryer to obtain surface amino graphite NH2-Gr; then put the surface amino graphite NH2-Gr into a stirring kettle filled with a phenolic resin aqueous solution with a solid content of 60% at a mass fraction of 15%, stir at a speed of 350r / min for 30 minutes and use 100kHz ultrasound for 4 hours to evenly disperse, then transfer to a water heating box at 90°C for constant temperature curing for 40 hours, and grind to Dv50 of about 10μm by a pulverizer to obtain a graphite curing material coated with resin carbon.
[0126] 2. Same as the step in Example 1.
[0127] 3. Same as the step in Example 1.
[0128] 4. Same as the step in Example 1.
[0129] Example 5 This embodiment provides a silicon-carbon composite negative electrode material, comprising the following steps: 1. Put artificial graphite powder and epoxy-containing silane coupling agent (γ-glycidyloxypropyltriethoxysilane) into a kettle reactor at a mass ratio of 1:3, heat to 100°C, keep warm for 12 hours, wash with deionized water to neutrality, and then dry in a vacuum dryer to obtain surface epoxylated graphite HO-Gr; then put the epoxylated HO-Gr into a stirring kettle containing a phenolic resin aqueous solution with a solid content of 60% at a mass fraction of 15%, stir at a speed of 350r / min for 30 minutes and use 100kHz ultrasound for 4 hours to evenly disperse, then transfer to a water heating box at 90°C for constant temperature curing for 40 hours, and grind to Dv50 of about 10μm by a pulverizer to obtain a graphite cured material coated with resin carbon.
[0130] 2. Same as the step in Example 1.
[0131] 3. Same as the step in Example 1.
[0132] 4. Same as the step in Example 1.
[0133] Example 6 This embodiment provides a silicon-carbon composite negative electrode material, comprising the following steps: 1. Put artificial graphite powder and silane coupling agent containing silicate (ethyl orthosilicate) into a kettle reactor at a mass ratio of 1:3, heat to 200°C, keep warm for 12 hours, wash with deionized water to neutrality, and then dry in a vacuum dryer to obtain surface modified graphite CHSiO-Gr; then put the modified CHSiO-Gr into a stirring kettle filled with a phenolic resin aqueous solution with a solid content of 60% at a mass fraction of 15%, stir at a speed of 350r / min for 30 minutes and use 100kHz ultrasound for 4 hours to evenly disperse, then transfer to a water heating box at 90°C for constant temperature curing for 40 hours, and grind to a Dv50 of about 10μm by a pulverizer to obtain a graphite curing material coated with resin carbon.
[0134] 2. Same as the step in Example 1.
[0135] 3. Same as the step in Example 1.
[0136] 4. Same as the step in Example 1.
[0137] Example 7 This embodiment provides a silicon-carbon composite negative electrode material, comprising the following steps: 1. Put artificial graphite powder and fluorine-containing silane coupling agent (heptadecafluorodecyltrimethoxysilane) into a kettle reactor at a mass ratio of 1:3, heat to 180°C, keep warm for 12 hours, wash with deionized water to neutrality, and then dry with a vacuum dryer to obtain surface fluorocarbon graphite FC-Gr; then put fluorocarbon graphite FC-Gr into a stirring kettle filled with a phenolic resin aqueous solution with a solid content of 60% at a mass fraction of 15%, stir at a speed of 350r / min for 30 minutes and use 100kHz ultrasound for 4 hours to evenly disperse, then transfer to a water heating box at 90°C for constant temperature curing for 40 hours, and grind to a Dv50 of about 10μm by a pulverizer to obtain a graphite curing material coated with resin carbon.
[0138] 2. Same as the step in Example 1.
[0139] 3. Same as the step in Example 1.
[0140] 4. Same as the step in Example 1.
[0141] Example 8 This embodiment provides a silicon-carbon composite negative electrode material, comprising the following steps: 1. Put artificial graphite powder and alcohol-containing silane coupling agent (γ-glycidyloxypropyltrimethoxysilane) into a kettle reactor at a mass ratio of 1:3, heat to 80°C, keep warm for 12 hours, wash with deionized water to neutrality, and then dry in a vacuum dryer to obtain surface alcohol-based graphite OR-Gr; then put the alcohol-based OR-Gr into a stirring kettle containing a phenolic resin aqueous solution with a solid content of 60% at a mass fraction of 15%, stir at a speed of 350r / min for 30 minutes and use 100kHz ultrasound for 4 hours to evenly disperse, then transfer to a water heating box at 90°C for constant temperature curing for 40 hours, and grind to a Dv50 of about 10μm by a pulverizer to obtain a graphite curing material coated with resin carbon.
[0142] 2. Same as the step in Example 1.
[0143] 3. Same as the step in Example 1.
[0144] 4. Same as the step in Example 1.
[0145] Comparative Example 1 This comparative example provides a silicon-carbon physical composite negative electrode material, comprising the following steps: 1. The phenolic resin solid was transferred to a pyrolysis rotary furnace, heated to 800°C at a heating rate of 10°C / min under a N2 atmosphere and kept warm for 6 hours, then transferred to an activation tube furnace, heated to 1200°C at a heating rate of 5°C / min under a H2O environment, and kept warm for 12 hours to obtain a phenolic resin porous carbon material.
[0146] 2. The porous carbon material was placed in a vertical fluidized bed. While continuously passing a N2 atmosphere for protection, monosilane gas was continuously introduced. The temperature was raised to 300°C at a heating rate of 5°C / min and kept warm for 9 hours to allow the mixed gas to evenly diffuse into the pores of the porous carbon. The temperature was then raised to 500°C and chemical vapor deposition was performed for 12 hours to obtain porous carbon with deposited silicon nanoparticles, in which the silicon content was 50%.
[0147] 3. After the deposition is completed and the temperature is lowered, the porous carbon with deposited silicon nanoparticles is transferred to a carbon-coated rotary furnace. In an atmosphere of a mixed gas of ethane and N2, the temperature in the furnace is raised to 700°C, and the graphite composite material with surface coated silicon-carbon is carbon-coated for 4 hours to obtain the phenolic resin silicon-carbon material, and the thickness of the carbon coating layer is 20 nm.
[0148] 4. The above phenolic resin silicon-carbon material and the graphite in the embodiment were put into a mechanical mixer at a ratio of 1:1 and physically mixed at 500 rpm / 20 min to obtain a graphite silicon-carbon mixed negative electrode material.
[0149] Test Case The silicon-carbon composite negative electrode materials prepared in the above examples and comparative examples were used as negative electrodes to assemble lithium batteries. The battery assembly was carried out in a glove box with a water and oxygen content of less than 0.1 ppm. Taking button battery CR2032 as an example: A slurry was prepared using graphite silicon-carbon integrated composite material as the active material, super p as the conductive agent, and PAA as the binder. The slurry was coated on a copper foil current collector to form a negative electrode. A lithium sheet was used as the counter electrode, Celgard 2500 was used as the separator, and 1 mol / LLiPF6 (volume ratio EC:DMC:DEC=1:1:1, containing an additional 5% volume of FEC) was used as the electrolyte to assemble the battery.
[0150] The electrochemical performance test was carried out at a constant temperature of 25°C, with a test voltage range of 0.005-1.5 V and a 0.1 C constant rate charge and discharge test.
[0151] The results are shown in Table 1 below: Table 1 Negative electrode performance test results of the embodiments and comparative examples
[0152] Based on Table 1, the graphite silicon-carbon integrated composite material prepared by the present invention has more excellent electrochemical performance. Example 1 is a graphite surface modification treatment, followed by nanoporous carbon coating and SiH4 deposition, with the ratio of graphite to surface silicon-carbon being 1:1, while Comparative Example 1 adopts a 1:1 physical mixing strategy, that is, graphite and silicon-carbon materials are physically mixed in a 1:1 ratio. The present invention mainly solves the problem of poor uniformity caused by the simple physical mixing strategy of graphite and silicon-carbon. The 0.1C specific capacity and 1C cycle data at room temperature show that this strategy can effectively alleviate the mixing uniformity problem caused by the difference in the surface characteristics of graphite and silicon-carbon, and can also greatly improve the cycle characteristics.
[0153] Characterization Example 1 The negative electrode material obtained in Example 1 was subjected to a scanning electron microscope, and the obtained image is as follows Figure 1 shown.
[0154] from Figure 1 It can be seen that the surface of each graphite particle is effectively coated with nanoporous silicon-carbon, and the particle morphology and structure are relatively more uniform and smooth, which greatly alleviates the uneven problem of the high compound ratio relationship between graphite and silicon-carbon, thereby improving the consistency of high energy density battery preparation and electrochemical performance.
[0155] Characterization Example 2 The negative electrode material obtained in Example 1 was subjected to backscattered electron imaging, and the obtained image is as follows Figure 2 shown.
[0156] from Figure 2 It can be seen that this method can effectively form a porous silicon-carbon composite structure on the graphite surface. There is no obvious light-dark contrast in the figure, indicating that the deposition uniformity between the particles is good. If this integrated composite negative electrode material is used, the negative electrode capacity can be improved while the uneven defects of the graphite-silicon-carbon physical mixing method can be improved, thereby greatly improving the battery cell production efficiency, battery cell consistency and interface stability of a single battery cell.
[0157] Characterization Example 3 The negative electrode material obtained in Example 1 was subjected to XRD, and the obtained picture is as follows Figure 3 shown.
[0158] from Figure 3 It can be seen that the XRD peak of the silicon-carbon composite negative electrode material is relatively raised by 20-50% compared with pure graphite, and obvious Si diffraction peaks appear near 28.4° and 47.5°, indicating that Si deposition behavior actually exists on the graphite surface. This further illustrates that the present method can construct a relatively uniform porous silicon-carbon structure on the surface of each graphite particle, thereby improving the local unevenness caused by the simple physical mixing of graphite-silicon-carbon, and further improving the consistency and stability of the negative electrode interface of the battery cell.
[0159] Results The first cycle electrical performance of the negative electrode material obtained in Example 1 is plotted as a graph. Figure 4 shown.
[0160] from Figure 4 It can be seen that the gram capacity of the silicon-carbon composite negative electrode material is much larger than the theoretical value of graphite (372 mAh / g). There is an obvious potential difference between the insertion and extraction of lithium between graphite and silicon-carbon. Simple physical mixing easily leads to the problem of poor uniformity in the connection of the insertion and extraction curves of lithium. The first-cycle electrical performance of the negative electrode obtained based on this method not only reflects the third-order charge and discharge mechanism of graphite, but also can gradually and evenly transition from 0.25V to the insertion and extraction potential range of lithium of silicon-carbon. Therefore, it is shown that the graphite silicon-carbon composite material prepared by this method has good integrated uniformity, thereby improving the dispersion uniformity of each particle at the electrode scale and the consistency of the battery cell.
[0161] Finally, it should be noted that the above-described embodiments are only specific implementations of the present invention, which are used to illustrate the technical solutions of the present invention, rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention is described in detail with reference to the above-described embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the above-described embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A silicon-carbon composite negative electrode material, characterized in that: It includes core layer, middle layer and shell layer; The material of the core layer is modified graphite, the middle layer is a silicon-carbon composite layer, and the shell layer is a carbon coating layer; In the silicon-carbon composite negative electrode material, the proportion of silicon is 5~30 wt%; in the X-ray diffraction spectrum Cu-Kα of the silicon-carbon composite negative electrode material, diffraction peaks are formed when 2θ is 26.5°, 28.4°, 45.0°, 47.5°, and 55.0°, wherein the ratio of the peak intensity at 2θ=26.5° to the peak intensity at 2θ=28.4° is ≤10, the half-peak width of the peak at 2θ=26.5° is 0.3°~0.8°, and the half-peak width of the peak at 2θ=28.4° is 0.3°~1.5°.
2. The silicon-carbon composite negative electrode material according to claim 1, characterized in that: Particle size is 2~50μm; The silicon-carbon composite layer comprises porous carbon and silicon deposited in the pores of the porous carbon; The porous carbon has a thickness ranging from 1 to 10 μm; In silicon-carbon composite negative electrode materials, the proportion of porous carbon is 15~30wt%; In the porous carbon, the pore size is 0.5-50 nm; The total pore volume of the porous carbon is 0.2-0.8 cm 3 / g.
3. The silicon-carbon composite negative electrode material according to claim 1, characterized in that: The modified graphite includes at least one of carboxylated graphite, hydroxylated graphite, oxidized graphite and ammoniated graphite.
4. A method for preparing the silicon-carbon composite negative electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: A. Putting modified graphite particles and porous carbon precursor into a liquid phase reactor and mixing them evenly, and then spray drying to obtain a composite material of modified graphite and carbon precursor; B. transferring the modified graphite and carbon precursor composite material into a high temperature reactor to carbonize and activate the carbon precursor to obtain a micron-sized modified graphite and nanoporous carbon composite material; C. Passing silane gas into a high-temperature reactor containing the micron-sized modified graphite and nanoporous carbon composite material to form a silicon-carbon composite layer on the surface of the modified graphite; continuing to pass hydrocarbon gas into the reactor for carbon deposition and coating to obtain a silicon-carbon composite negative electrode material.
5. The preparation method according to claim 4, characterized in that: The preparation method of the modified graphite particles is: Placing graphite and a surface modifier in a solid-liquid reactor, performing surface modification treatment on the graphite, and then drying to obtain modified graphite particles; The particle size of the graphite is 2-40 μm; The solid-liquid reactor includes a tank reactor, a tubular reactor or a fluidized bed reactor; The surface modification temperature is 20-150°C; The drying method includes spray drying, flash drying, rotary drying, fluidized bed drying or vacuum drying.
6. The preparation method according to claim 5, characterized in that: The graphite includes artificial graphite and / or natural graphite; The natural graphite includes at least one of dense crystalline graphite, flake graphite and cryptocrystalline graphite; The surface modifier includes an inorganic solution and / or an organic solution; The inorganic solution includes hydrogen peroxide and / or nitric acid; The organic solution includes a silane coupling agent; The functional groups in the silane coupling agent include at least one of ethoxy, amino, epoxy, silicate, fluorocarbon and alcohol.
7. The preparation method according to claim 4, characterized in that: The porous carbon precursor includes at least one of polyacrylonitrile, phenolic resin, melamine resin, epoxy resin, urea-formaldehyde resin, polyester resin, polyamide resin, polyimide resin, polycarbonate, and acrylonitrile copolymer; The specific surface area of the micron-sized modified graphite and nanoporous carbon composite material is 0.5-10 m 2 / g; The pores in the porous carbon include micropores and mesopores; The size of the pores in the porous carbon is 0.5 to 50 nm; The pore volume of the porous carbon is 0.2-0.8 cm 3 / g.
8. The preparation method according to claim 4, characterized in that: The silane gas includes at least one of monosilane, disilane, trichlorosilane and dichlorosilane; The hydrocarbon gas includes at least one of methane, ethane, propane, butane, ethylene, propylene and acetylene.
9. The preparation method according to claim 4, characterized in that: The liquid phase reactor comprises a pipeline reactor or a stirred tank; The temperature of the liquid phase reactor is 20-400°C; The high temperature reactor includes a rotary kiln, a pusher kiln, a roller kiln, a box furnace or a tube furnace; The carbonization temperature is 400-1500°C; Passing activation gas to perform the activation; The activated gas comprises at least one of carbon dioxide, flue gas, water vapor, air and oxygen; The activation temperature is 600-1200°C.
10. The preparation method according to claim 4, characterized in that: The temperature of the carbon deposition coating is 400-1000°C; The thickness of the carbon coating formed by carbon deposition coating is 0.5~50 nm; The carbon increment after carbon deposition coating is 0.1~5%.
Citation Information
Patent Citations
Preparation method of graphene doped silicon carbon material
CN118763211A
Graphite / silicon composite material and preparation and application thereof
CN118867170A
Porous carbon-graphite composite material, preparation method thereof, silicon-carbon material and electrochemical device
CN119008255A
Method of producing graphene-carbon hybrid foam-protected anode active material coating for lithium-ion batteries
US20200235393A1
Method for preparing silicon-carbon composite material using negative electrodes of waste lithium-ion batteries and application
WO2022179292A1